Gene sequencing and in silico characterization of mannose-binding lectin in South African chicken breeds (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: To sequence and characterize the mannose-binding lectin gene of three South African chicken breeds, namely, Potchefstroom Koekoek (PK), Venda (VN), and Ovambo (OV), to ascertain their genetic and immunologic diversity. Materials and Methods: Total RNA was isolated from hepatic samples, quantified, and reverse-transcribed to generate cDNA. The MBL gene was amplified by PCR, confirmed by gel electrophoresis, purified, and sequenced using Sanger sequencing. Sequences were analyzed with FinchTV and submitted to GenBank. Comparative sequences were retrieved from National Centre for Biotechnology Information for multiple sequence alignment and phylogenetic analysis using MEGA. ProtParam and ExPASy were used for physicochemical analysis. Secondary structures were predicted using PDBsum, while tertiary structures were modeled with Swiss-Model, refined by GalaxyWEB, and validated by ProSA. Functional domain analysis, binding site prediction, and ligand interaction studies were also performed. Results: MBL sequences showed breed-specific differences in protein length, isoelectric points, and thermostability. PK and VN MBLs had acidic pI values (< 7), while OV displayed a higher, alkaline pI. Conserved Glu–Pro–Asn (EPN) and Trp–Asn–Asp (WND) residues, linked by calcium ions, were identified for mannose-binding. Phylogenetic analysis revealed that PK breeds clustered closely with the White Leghorn (95%), OV clustered nearby PK breeds and Leghorn (82%), while VN clustered more closely with Indian Assel breeds (96%). Two conserved motifs (IPR033990 and IPR001304) were detected. Secondary and tertiary structuresrevealed predominant random coils in PK and OV, and more alpha-helices in VN. Binding site analysis identified key regions likely involved in immune modulation. Conclusion: This research reveals variation in MBL genes and their immune relevance in South African chicken breeds, offering a basis for breeding strategies.J. Adv. Vet. Anim. Res., 12(3): 941–955, September 2025http://doi.org/10.5455/javar.2025.l955